Toxicity Activity and Total Phenolic Content of Soursop Leaves from Three Regions in South Sulawesi, Indonesia - Rasyid, Faradiba Abdul; Amin, Asni; Sukmawati, Sukmawati; Djakariani, Kurnia Putri; Riska, Riska; Aliansyah, Moch. Rayhan; Sari, Cindy Artika (Poltekkes Kemenkes Gorontalo, 2023)
The fruit plant known as the soursop (Annona muricata L.) is indigenous to the Caribbean, Central America, and South America. The leaves of soursop contain substances with the potential to be cytotoxic, such as phenols and anonaceous acetogenins. Numerous variables, including geographic location, climatic conditions, and pest or disease disturbance factors, might impact a compound's phenol levels and toxicity. This study aims to investigate whether there are variations in the phenolic content and toxicity of the ethanol extract of soursop leaves that are grown in Gowa, Takalar, and Pinrang, three distinct regions in South Sulawesi, Indonesia. The Folin-Ciocalteu reagent was used to evaluate the total phenolic content, whereas Artemia salina Leach larvae were used for the BSLT method of the toxicity test. The results showed that the extracts of soursop leaves from Gowa, Pinrang, and Takalar had total phenolic contents of 3.7588% mg GAE/g, 0.9686% mg GAE/g, and 1.3832% mg GAE/g, respectively. Gowa, Pinrang, and Takalar have LC50 values of 38.19 µg/mL, 34.35 µg/mL, and 70.95 µg/mL, respectively, indicating their toxicity. The conclusion is that there were differences in the phenolic content and toxicity level of the ethanol extract of soursop leaves. All of these areas could source raw materials of soursop for the development of herbal medicines with cytotoxicity, i.e., anticancer, because they have LC50< 1,000 µg/mL.